Notes on the tribe Petrognathini Blanchard, 1845 from China, with description of a new species from Yunnan (Coleoptera, Cerambycidae, Lamiinae) - Bi, Wen-Xuan; Chen, Chang-Chin; Lin, Mei-Ying (Zootaxa, 2020)
Ithocritus ruber (Hope, 1839), the type species of the genus Ithocritus Lacordaire, 1872 is reinvestigated, and a partially sympatric species, Ithocritus similis Bi & Lin, sp. nov. (相似短柄天牛, Xiāng sì duǎn bǐng tiān niú), is described. The genus Falsimalmus Breuning, 1956 is newly recorded from China, based on the discovery of Falsimalmus niger Breuning, 1956 from Yunnan. New localities, illustrations of habitus, endophallic structure and major diagnostic features for all involved taxa are provided.